2020
DOI: 10.3390/molecules25122834
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Microalgae and Cyanobacteria: Effect of Operating Conditions on Growth and Biomass Composition

Abstract: The purpose of this work is to define optimal growth conditions to maximise biomass for batch culture of the cyanobacterium Arthrospira maxima and the microalgae Chlorella vulgaris, Isochrysis galbana and Nannochloropsis gaditana. Thus, we study the effect of three variables on cell growth: i.e., inoculum:culture medium volume ratio (5:45, 10:40, 15:35 and 20:30 mL:mL), light:dark photoperiod (8:16, 12:12 and 16:8 h) and type of culture medium, including both synthetic media (Guillard’s F/2 and Walne’s) and wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 60 publications
2
27
0
Order By: Relevance
“…(clone T. ISO ), Pavlova lutheri , and Nannochloropsis oculata , the protein accumulation was enhanced during the exponential phase but started to decline during the stationary phase [ 117 ]. Protein accumulation in the biomasses of C. vulgaris and N. gaditana was maximized during exponential growth but declined for C. vulgaris four days into the stationary growth phase [ 118 ]; this reaffirms the important effect of the growth phase on final biomass protein content. An optimal harvest time in the exponential phase should be determined by assessing both the accumulation rate and total yield to achieve the maximal protein production rate.…”
Section: Protein Content Of Microalgae Collected At Different Growth Phasesmentioning
confidence: 86%
“…(clone T. ISO ), Pavlova lutheri , and Nannochloropsis oculata , the protein accumulation was enhanced during the exponential phase but started to decline during the stationary phase [ 117 ]. Protein accumulation in the biomasses of C. vulgaris and N. gaditana was maximized during exponential growth but declined for C. vulgaris four days into the stationary growth phase [ 118 ]; this reaffirms the important effect of the growth phase on final biomass protein content. An optimal harvest time in the exponential phase should be determined by assessing both the accumulation rate and total yield to achieve the maximal protein production rate.…”
Section: Protein Content Of Microalgae Collected At Different Growth Phasesmentioning
confidence: 86%
“…The algal biomass increases with the culture time [ 71 ]. Hu et al showed that the maximum harvesting efficiency could be obtained on days 14–18, i.e., when the biomass reaches the peak value [ 70 , 72 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, some authors indicated that the f/2 medium is not suitable for cyanobacterial culture [ 41 ]. On the other hand, there are studies that confirm that cyanobacteria achieved the highest biomass on the f/2 medium [ 42 ]. Regardless of the medium used, it is possible that nutrient enrichment from the macroalgal extract may provide essential growth-related nutrients to cyanobacterial cells.…”
Section: Discussionmentioning
confidence: 99%